2001
DOI: 10.1614/0043-1745(2001)049[0792:hroadr]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Host range of a deleterious rhizobacterium for biological control of downy brome

Abstract: Pseudomonas fluorescens strain D7 (P. f. D7; NRRL B-18293) is a root-colonizing bacterium that inhibits downy brome (Bromus tectorum L. BROTE) growth. Before commercialization as a biological control agent, strain D7 must be tested for host plant specificity. Agar plate bioassays in the laboratory and plant–soil bioassays in a growth chamber were used to determine the influence of P. f. D7 on germination and root growth of 42 selected weed, cultivated or native plant species common in the western and midwester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(36 citation statements)
references
References 28 publications
3
32
0
1
Order By: Relevance
“…The number of DRBs belongs to the genus of Aeromonas, Agrobacterium, Alcaligenes, Bacillus, Burkholderia, Chryseomonas, Enterobacter, Microbacterium, Pseudomonas and Xanthomonas were reported by several studies [12][13][14]. On the other hand, the deleterious effect of bacterium on plants can be species or cultivars specific [15]. For this reason, we tested the bacterial isolate I-3 and I-4-5 on lettuce to confirm their deleterious effect.…”
Section: Discussionmentioning
confidence: 91%
“…The number of DRBs belongs to the genus of Aeromonas, Agrobacterium, Alcaligenes, Bacillus, Burkholderia, Chryseomonas, Enterobacter, Microbacterium, Pseudomonas and Xanthomonas were reported by several studies [12][13][14]. On the other hand, the deleterious effect of bacterium on plants can be species or cultivars specific [15]. For this reason, we tested the bacterial isolate I-3 and I-4-5 on lettuce to confirm their deleterious effect.…”
Section: Discussionmentioning
confidence: 91%
“…Research on alternative methods are in their infancy, but can produce practical results, e.g., microbial herbicides [174,175]. For example, organic agriculture suffers a yield gap compared to conventional agriculture, but use of Best Management Practices minimizes this gap [176].…”
Section: Strategy 3 Cultivate Production Systems Robust To Multiple mentioning
confidence: 99%
“…After finding that only two plant species were inhibited, they concluded that A. alternata would not be harmful to any economically important plants. Kennedy et al (2001) found that Pseudomonas fluorescens strain D7 inhibited the target weed, downy brome, a few other Bromus species, jointed goatgrass and medusahead (Taeniatherum caput-medusae) in bioassays, greenhouse and field studies. They investigated representatives from a wide array of families that included native, crop and weed species, while concentrating on familes, tribes, subtribes and accessions closely related to Bromus species.…”
Section: Challenges For Weed Control With Microbial Herbicidesmentioning
confidence: 99%